Long-term spectroscopy of [eta] Carinae - I. The high and low excitation phases - Damineli, Augusto; Stahl, Otmar; Kaufer, Andreas; Wolf, Bernhard (Astronomy & astrophysics. Supplement series, 1998)
Astronomy and Astrophysics, Supplement Series (A&AS) published data papers, either observational or theoretical, as well as extensive data material forming the basis of papers with astrophysical results
Gesehen am 09.06.2017